Utilizing Roadmaps in Evacuation Planning - Rodriguez, Samuel; Amato, Nancy M. (International Journal of Virtual Reality, 2011)
In this paper we describe utilization of roadmaps in a general evacuation planning system for complex 3D environments. The problem consists of heterogeneous groups of agents whose behaviors and properties affect usage of the environment when creating evacuation plans. This planning system includes behaviors for those agents evacuating and directors that may be guiding the agents to improve evacuation. One aspect we focus on is modeling different forms of direction and communication between agents.